The category of node-and-choice preforms for extensive-form games - Peter Alfred Streufert (The University of Western Ontario, Department of Economics, 2016)
It would be useful to have a category of extensive-form games whose isomorphisms specify equivalences between games. Since working with entire games is too large a project for a single paper, I begin here with preforms, where a "preform" is a rooted tree together with choices and information sets. My first contribution is to introduce a compact preform spec ification called a "node-and-choice" preform. This specification's compactness allows me to introduce tractable morphisms which map one node-and-choice preform to another. I incorporate these morphisms into a category called the "category of node-and-choice preforms". Finally, I characterize the isomorphisms of this category
Keywords: C72; 330; game form; isomorphism